Implementasi Tanggung Jawab Sosial Perusahaan dalam Mewujudkan Prinsip Maslahah dan Keseimbangan Ekologis di Kota Makassar - Magun Pikahulan, Rustam; Kurniati; Misbahuddin; Rasyid, St. Cheriah; Anisa, Nur Ainun (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2025)
Makassar City, as a central socio-economic hub in Eastern Indonesia, faces a development paradox that is rapid progress in industry, trade, and investment has simultaneously generated severe environmental pressures. Massive urbanization has led to the reduction of green spaces, an increase in waste production reaching 868 tons per day, and recurring floods caused by spatial violations. This study examines the implementation of Corporate Social Responsibility (CSR) through the lens of maslahah and ecological balance, aiming to achieve social and environmental justice. The research employs a field research design, utilizing normative and empirical juridical methods, which include observation, interviews, and document analysis based on legal frameworks such as Law No. 40 of 2007 and Makassar Regional Regulation No. 2 of 2016. The findings indicate that CSR in Makassar serves as an ethical, legal, and spiritual instrument for realizing maqāṣid al-sharī‘ah, particularly hifz al-nafs (protection of life) and hifz al-bi’ah (environmental preservation). CSR practices, including waste management and environmental education, embody the principles of dar’ al-mafāsid (preventing harm) and jalb al-masālih (promoting benefit), affirming CSR’s role in fostering collective welfare and ecological justice toward sustainable development grounded in Islamic values.